Teksty literatury wysokiej w odbiorze uczniowskim w świetle ankiety - Krasińska, Aneta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
Amongst the literary works being discussed on the different levels of education, there are both popular and highly artistic ones. Gradually children are being introduced to the literary pieces which they rather don't come across daily. It is a Polish language teacher who initiates a young reader into various genres of highly artistic literature. Thanks to his actions every genre of the highly artistic literature illustrated with the represented example has a chance to be received in a positive way by a reader.